Entering the “foxhole”: Partisan media priming and the application of racial justice in America - Andrew M. Bell; Christopher D. DeSante; Thomas Gift; Candis Watts Smith (Research & Politics)
Can accessing a partisan media environment—irrespective of its content—change how Americans interpret and assess news? We examine this question by focusing on one of the most fraught issues in American society: racial justice. Although studies suggest that repeated exposure to right-leaning media messaging can amplify racial resentment, we leverage a pair of survey experiments to test whether merely seeing a conservative media masthead can make Whites render justice with racialized considerations. Results show that—even keeping the content of stories identical—entering a simulated right-leaning media environment significantly conditions racial attitudes. We find evidence of both anti-Black and pro-White biases that are activated when respondents consume information under the Fox News masthead. This study has important implications for understanding how partisan media priming shapes political views and the distinctive nature of racism in America.